235k views
3 votes
. Simplify (4x + 2)3.

User Ramon Snir
by
6.0k points

2 Answers

1 vote

Answer:

Explanation:

Multiply 3 times 4x which gives you 12. Multiply 3 times 2 which gives you 6. Your final answer is 12x+6

User Zappescu
by
5.1k points
2 votes

Answer:


(4x+2)^3=64x^3+96x^2+48x+8

Explanation:

Given : Expression
(4x+2)^3

To find : Simplify the expression ?

Solution :

Expression
(4x+2)^3

Applying cubic identity,


(a+b)^3=a^3+b^3+3a^2b+3ab^2


(4x+2)^3=(4x)^3+(2)^3+3(4x)^2(2)+3(4x)(2)^2


(4x+2)^3=64x^3+8+96x^2+48x


(4x+2)^3=64x^3+96x^2+48x+8

Therefore, Simplification is
(4x+2)^3=64x^3+96x^2+48x+8

User BillyJoe
by
6.4k points